2015
DOI: 10.1017/psrm.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electoral Systems on Voter Turnout: Evidence from a Natural Experiment

Abstract: I exploit the unique institutional framework of Spanish local elections, where municipalities follow different electoral systems depending on their population size, as mandated by a national law. Using a regression discontinuity design, I compare turnout under closed-list proportional representation and under an open-list, plurality-at-large system where voters can vote for individual candidates from the same or different party lists. I fi nd that the openlist system increases turnout by between one and two pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 73 publications
(100 reference statements)
0
17
0
Order By: Relevance
“…Other municipalities use an open-list system and are excluded from our sample. Sanz (2017) and Gonzalez-Eiras and Sanz (2018) estimate the effects of the change in electoral rules at the 250-person cutoff on turnout and women's representation, respectively.…”
Section: Importance Of Municipal Governments Municipal Governments Mmentioning
confidence: 99%
“…Other municipalities use an open-list system and are excluded from our sample. Sanz (2017) and Gonzalez-Eiras and Sanz (2018) estimate the effects of the change in electoral rules at the 250-person cutoff on turnout and women's representation, respectively.…”
Section: Importance Of Municipal Governments Municipal Governments Mmentioning
confidence: 99%
“…We carefully address the concerns they raise. Similar to us, Sanz (2017) and Lyytikäinen and Tukiainen (2016) use population thresholds to study political consequences of electoral systems.…”
Section: Identification Strategy and Estimationmentioning
confidence: 99%
“…Using a regression discontinuity approach and official elections' data from Spanish municipalities, Sanz (2017) shows that turnout is higher when voters can cast preference However, evidence regarding how ballot structure affects satisfaction with democracy is mixed. The first study on the topic by Farrell and McAllister (2006) found that levels of satisfaction with democracy tended to be higher in list PR systems allowing voters to cast votes for candidates.…”
Section: Voting and Satisfaction With Democracy Under Prmentioning
confidence: 99%